Social Harmony In Maintaining Interfaith Harmony From The Perspective Of Maqashid Syari'ah In Jambi - Yeni Fatma Sabli; Latif, Mukhtar; Pauzi, Pauzi (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
Social harmony is essential for fostering peaceful coexistence in multicultural societies, particularly in regions with diverse religious backgrounds like Jambi Province, Indonesia. This study investigates the role of Maqashid Syari'ah Islamic legal objectives in promoting interfaith harmony and social cohesion. This study employs a qualitative approach to explore the concept of social harmony and its significance in promoting inter-religious coexistence, specifically within the context of Maqashid Syari'ah in Jambi Province. The study highlights the importance of collective commitment from various societal actors, including religious leaders, community organizations, and local governments, in promoting interfaith dialogue and understanding. The research identifies practical strategies for enhancing social cohesion, such as community engagement initiatives and educational programs emphasizing shared values and mutual respect among religious groups. This study underscores the relevance of Maqashid Syari'ah as a guiding framework for addressing contemporary challenges of intolerance and radicalism in Jambi Province. By promoting social harmony through the lens of Islamic teachings, the research offers valuable insights and practical solutions that can be adapted to other regions facing similar challenges. Fostering a tolerance and cooperation culture is vital for achieving sustainable peace and stability in diverse societies.